2022
DOI: 10.1111/cts.13264
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variation in HLA‐DRB1 is associated with development of antidrug antibodies in cancer patients treated with atezolizumab that are neutralizing in vitro

Abstract: The treatment of diseases with biologic agents can result in the formation of antidrug antibodies (ADA). Although drivers for ADA formation are unknown, a role for antigen presentation is likely, and variation in human leukocyte antigen (HLA) genes has been shown to be associated with occurrence of ADA for several biologics. Here, we performed an HLA-wide association study in 1982 patients treated with the anti-PD-L1 antibody atezolizumab across eight clinical trials. On average, 29.8% of patients were ADA-pos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…ICIs were also shown to generate ADA responses in patients with cancer [91,[93][94][95]. Among the various ICI antibodies, atezolizumab has the highest incidence rate of ADA (29.8%) compared to others (around 5% to 10%) [18,90,91,96]. The results of the IMbrave 150 study showed that the incidence of atezolizumab ADA reached 29.6% in patients with HCC at one or more timepoints following atezolizumabbevacizumab treatment [97].…”
Section: Anti-drug Antibody Against Atezolizumabmentioning
confidence: 99%
“…ICIs were also shown to generate ADA responses in patients with cancer [91,[93][94][95]. Among the various ICI antibodies, atezolizumab has the highest incidence rate of ADA (29.8%) compared to others (around 5% to 10%) [18,90,91,96]. The results of the IMbrave 150 study showed that the incidence of atezolizumab ADA reached 29.6% in patients with HCC at one or more timepoints following atezolizumabbevacizumab treatment [97].…”
Section: Anti-drug Antibody Against Atezolizumabmentioning
confidence: 99%